Negativity towards Wilderness in the Biblical Record - Leal, Robert Barry (Journal for the Study of Religion, Nature and Culture, 2005)
In recent ecotheological writing little attention has been paid to the phenomenon of wilderness. This is surprising when one considers the centrality of wilderness to a theology of creation. Traditional Western attitudes to wilderness have emphasized conflict and domination rather than respect and collaboration. In some powerful political circles (such as the Bush Administration) such resistance to the natural order continues to be seen as grounded in the Bible and hence to be theologically justified. For these reasons it is important to address the various wilderness traditions that one encounters in the Bible and in particular to acknowledge the negativity that is present. Only when such negativity is taken into account and placed in context will a convincing, biblically-based, contemporary theology of creation be able to emerge. Negative attitudes towards wilderness are identified in the Pentateuch, in several of the prophets, in Job and in the New Testament, and their implications for theology suggested. While it is recognized that such a diverse collection of books as the Bible also contains other than negative attitudes towards wilderness, this article focuses on negativity as an attitude in need of highlighting and addressing in contemporary circumstances.